Influence of structure 3,5,7,3',4'–Pentahydroxyflavone-based polymer films on their optical transparency - Mishurov, Dmytro; Voronkin, Andrii; Roshal, Alexander; Bogatyrenko, Sergey (My University, 2017)
Optical properties and morphology of polymer films based on diglycidyl ether of bis-phenol A and on natural compound 3,5,7,30 ,40 epentahydroxyflavone (quercetin) using UVevis spectroscopy, scanning electron microscopy and powder X-ray diffraction methods have been investigated. The influence of ordering degree of the polymers, flexibility of their chains, intensity of intermolecular interaction between the quercetine moieties on the polymers' morphology was discussed. It is shown that all the quercetine-based polymer films are transparent at visible and near infrared regions beginning from 420 to 450 nm. Low optical transparency in the short-wavelength region can be explained the self-absorption of quercetin moieties in the polymer chains

Досліджено оптичні властивості та морфологію полімерних плівок на основі дигліціділового ефіру біс-фенолу А та природного з'єднання 3,5,7,3′,4′–пентагідроксифлавону (кверцетину) за допомогою УФ–віс-спектроскопії, скануючої електронної мікроскопії та порошкової дифракції рентгенівських променів. Розглянуто вплив ступеня упорядкування полімерів, гнучкості їх ланцюгів, інтенсивності міжмолекулярної взаємодії між кверцетинними муетами на морфологію полімерів. Показано, що всі полімерні плівки на основі кверцетину прозорі у видимих і ближніх інфрачервоних областях, починаючи від 420 до 450 нм. Низькою оптичною прозорістю в короткохвильової області можна пояснити самопоглинання кверцетинових муетів в полімерних ланцюгах.
Keywords: cross-linked polymers; heterogeneity; optical transparency; globular clusters; quercetin; зшиті полімери; неоднорідність; оптична прозорість; глобулярні кластери; кверцетин